2021
DOI: 10.1055/s-0040-1718781
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between Transforaminal Lumbar Interbody Fusion and Posterolateral Fusion for Treatment of Spondylolisthesis: Clinical Outcomes and Spino-Pelvic Sagittal Balance Parameters

Abstract: Objective This retrospective study aims to compare the clinical and radiological outcomes of posterolateral fusion (PLF) with transforaminal lumbar interbody fusion (TLIF + PLF) for the treatment of patients with low-grade spondylolisthesis. Methodology A total of 77 adult patients ≥18 years with low-grade spondylolisthesis, Meyerding grades I and II, were assigned into two groups: 36 patients treated with PLF and 41 patients treated with TLIF + PLF. The PLF group is composed of the patients that were operated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Yadav et al (2020) showed comparable results that TLIF surgical procedure was found better than PLF regarding back pain and the results were found statistically significant (P<0.001). A similar scenario was also reported in a study carried out by Farrokhi et al, 17 who confirmed that the TLIF technique was found better than PLF regarding pain with statistically significant results (P = 0.0001). Farid and Elkholy 25 exhibited similar outcomes according to the VAS score, patients treated with the TLIF technique had more relief in pain than the PLF group and the results were statistically significant.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Yadav et al (2020) showed comparable results that TLIF surgical procedure was found better than PLF regarding back pain and the results were found statistically significant (P<0.001). A similar scenario was also reported in a study carried out by Farrokhi et al, 17 who confirmed that the TLIF technique was found better than PLF regarding pain with statistically significant results (P = 0.0001). Farid and Elkholy 25 exhibited similar outcomes according to the VAS score, patients treated with the TLIF technique had more relief in pain than the PLF group and the results were statistically significant.…”
Section: Discussionsupporting
confidence: 89%
“…However, Yadav et al, 26 reported that in the PLF group, the mean age of the patients was 47 years while in the TLIF group was 48 years. Farrokhi et al, 17 highlighted that in the PLF group, the mean age of the patients was 55 years while in the TLIF group, the mean age of patients was 52 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive effect of TLIF surgery in pain control and improvement in quality of life is also supported by other studies. 17 Regarding variables related to patient characteristics, only BMI ! 30 Kg/m 2 influenced the functional outcome, as obese patients had higher degree of disability at M6.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of TLIF surgery in pain control and improvement in quality of life is also supported by other studies. 17…”
Section: Discussionmentioning
confidence: 99%